Resveratrol ameliorates maternal immune activation-associated cognitive impairment in adult male offspring by relieving inflammation and improving synaptic dysfunction - Zhang, Yue-Ming; Wei, Ru-Meng; Zhang, Meng-Ying; Zhang, Kai-Xuan; Zhang, Jing-Ya; Fang, Shi-Kun; Ge, Yi-Jun; Kong, Xiao-Yi; Chen, Gui-Hai; Li, Xue-Yan (Frontiers in Behavioral Neuroscience, 2023)
Maternal exposure to inflammation may represent a major risk factor for neuropsychiatric disorders with associated cognitive dysfunction in offspring in later life. Growing evidence has suggested that resveratrol exerts a beneficial effect on cognitive impairment via its anti-inflammatory and antioxidant properties and by ameliorating synaptic dysfunction. However, how resveratrol affects maternal immune activation-induced cognitive dysfunction and the underlying mechanisms are unclear. In the present study, pregnant dams were given an intraperitoneal injection of lipopolysaccharide (LPS; 50 µg/kg) on gestational day 15. Subsequently, the offspring mice were treated or not with resveratrol (40 mg/kg) from postnatal day (PND) 60 to PND 88. Male offspring were selected for the evaluation of cognitive function using the Morris water maze test. The hippocampal levels of pro-inflammatory cytokines were examined by ELISA. The mRNA and protein levels of sirtuin-1 (SIRT1), brain-derived neurotrophic factor (BDNF), postsynaptic density protein 95 (PSD-95), and synaptophysin (SYP) were determined by RT-qPCR and western blot, respectively. The results showed that male offspring mice exposed to LPS in utero exhibited learning and memory impairment. Additionally, the levels of interleukin (IL)-1β, IL-6, and tumor necrosis factor-alpha (TNF-α) were increased while those of SIRT1, BDNF, PSD-95, and SYP were decreased in male offspring of LPS-treated mothers. Treatment with resveratrol reversed the cognitive impairment and attenuated the increase in the levels of pro-inflammatory cytokines induced by maternal immune activation in the offspring mice. Furthermore, resveratrol reversed the deleterious effects of maternal immune activation on SIRT1, BDNF, PSD-95, and SYP levels in the hippocampus. Collectively, our results suggested that resveratrol can effectively improve learning and memory impairment induced by maternal immune activation via the modulation of inflammation and synaptic dysfunction. resveratrol in mild cognitive impairment and Alzheimer's disease: A systematic review.Journal of medicinal food, 25(8),